Solve the equation (dy/dx) − y = exy2
"\\frac{dy}{dx} - y = (e^x)y^2" ...(1)
taking "y = \\frac{1}{v}"
"\\frac{dy}{dx}=-\\frac{1}{v^2}.\\frac{dv}{dx}"
From (1)
"-\\frac{1}{v^2}.\\frac{dv}{dx}-\\frac{1}{v}=e^x.\\frac{1}{v^2}"
"\\frac{dv}{dx}+v=-e^x...(2)"
The integrating factor "=e^{\\int1dx}=e^x"
Thus, the solution of (2) is
"v.e^x=\\int(-e^x).e^xdx+c"
"v.e^x=-\\int e^{2x}dx+c"
"v.e^x=-\\frac{ e^{2x}}{2}+c"
"\\frac{e^x}{y}=-\\frac{ e^{2x}}{2}+c"
"\\frac{1}{y}=\\frac{ -e^{x}+2c.e^{-x}}{2}"
"y=\\frac{2}{ -e^{x}+2c.e^{-x}}"
Comments
Leave a comment